Procrastination and Problematic Internet Use - Utami, Dessy Nur (ANIMA Indonesian Psychological Journal, 2013)
Problematic Internet use is the degree of comfort of a person in using Internet than living his life in the real world. The purpose of this study was to test Temporal Motivation Theory (TMT) by correlating problematic Internet use and procrastination. Subjects were psychiology students (N=131) who took Measurement Instrument Construction (MIC) course. Data were obtained by using the Pure Procrastination Scale (PPS), Online Cognition Scale (OCS), and Steel Procrastination Scale (SPS). Results revealed a positive correlation between procrastination and problematic Internet use (r = .370, p < .05). The main variables in the correlation originated from the distraction aspect. Results showed that the correlation between procrastination and problematic Internet use was not mediated by expectancy, value, and sensitivity to delay. Penggunaan Internet bermasalah merupakan tingkat kenyamanan seseorang dalam menggunakan Internet dibandingkan dengan kehidupannya di dunia nyata. Tujuan studi ini adalah untuk menguji Temporal Motivation Theory (TMT) dengan menghubungkan penggunaan Internet bermasalah dan prokrastinasi. Subjek penelitian adalah mahasiswa psikologi (N=31) yang mengambil mata kuliah PAU (Penyusunan Alat Ukur) pada semester genap tahun ajaran 2011/2012. Data diperoleh dengan menggunakan skala Pure Procrastination Scale (PPS), Online Cognition Scale (OCS), dan Steel Procrastination Scale (SPS). Pada studi ini ditemukan adanya korelasi positif antara prokrastinasi dan penggunaan Internet bermasalah (r = .370, p < .05). Variabel utama dalam korelasi ini berasal dari aspek distraksi. Hasil menunjukkan bahwa hubungan antara prokrastinasi dan penggunaan Internet bermasalah bukan dijembatani oleh aspek expectancy, value, dan sensitivity to delay.